Experimental Study of the Combustion of Kerosene and Binary Surrogate in the Model Combustion Chamber - Sergey S. Matveev; Ivan V. Chechet; Aleksander S. Semenikhin; Valerii Y. Abrashkin; Sergey V. Lukachev; Sergey G. Matveev (Journal of Combustion)
The purpose of this paper is to conduct experimental research of hazardous substance emissions at the simulated combustion chamber output. The experiment was carried in a simulated combustion chamber. The combustion chamber included a burner device; a liquid fuel feed system; and a flame tube with two rows of mixing holes and one row of cooling holes. The combustion chamber operation mode was φ = 0.435, Tpreheat = 423 K, and the atmospheric pressure. The liquid fuel burn rate was 0.77 g/s. The pressure ratio in the combustion chamber remained constant at ΔP = 3%. Two types of fuel were used: aviation kerosene of Russia’s TS-1 brand and the fuel surrogate was n-decane mixture (C10H22) with benzene additions (C6H6). The benzene additions were 5% through 30% (n-decane/benzene: 95/5, 90/10, 85/15, 80/20, 75/25, and 70/30).